Сurrent Issues in Sebaceous Sweat Fingerprint Residue Visualization on Fired Cartridge Cases - I. V. Latyshov; V. A. Vasil’ev; D. A. Evstropov; M. S. Stanovoi (Теория и практика судебной экспертизы, 2019)
This article focuses on issues concerning discovery of hands deposits on cases fred with certain models of fre weapons – 5.45 mm assault riﬂe АК-74М, 9 mm Makarov gun, 7,62 mm TT gun. Five persons left in turn on each of the above ammunition rounds intentionally qualitative hand traces, following which a shot was fred. After the shot the fre shot cases were collected and packed, avoiding contact between side surfaces and package material. The possibilities of discovery hand deposits on fred cases were determined by using reductive-oxidative and physical-chemical methods. The mechanism of “latent degradation” of hand deposits on cases formed before fring caused by the inﬂuence of the shot fact (high temperature, static and dynamic power contact of fred case with gun chamber walls) has been reviewed.